Microstructure analysis of electrokinetically stabilized peat - Moayedi, Hossein; Nazir, Ramli; Kazemian, Sina; Kim Huat, Bujang (Elsevier, 2014)
In this research, four new chemical grout reagents were used, namely, sodium silicate, calcium chloride, calcium oxide, and aluminium hydroxide. The injection of the chemicals through the soil by using an electrokinetic method was successfully performed. Increase in the shear strength of stabilized soil was higher in the locations near the cathode and the calcium oxide showed the highest increment. The soil microstructure is comprehensively changed due to the change in the pH of the soil, and fluid flow during the electrokinetic application depends upon time and location of samples taken along the cell. The EDX output of natural peat showed the presence of oxygen (46.2%), carbon (29.3%), silica (5.1%), alumina (2.5%), and calcium (3.0%). However, after electrokinetic injection of the sodium silicate, calcium oxide, calcium chloride, and aluminium hydroxide, the concentration of these elements in the soil samples taken adjacent to the anode changed, with the carbon changing to 24.9%, 16.5%, 31.4%, 34%; the oxygen to 47.6%, 41.9%, 53%, 46%; the silica to 12.3%, 4.1%, 4.2%, 4.7%; the alumina to 2.5%, 1.2%, 2.2%, 6.2%; and the calcium to 1.8%, 18.6%, 6.1%, 2.6%, respectively.